Serum Angiopoeitin Like-4 As An Early Detection Marker Of Diabetic Kidney Disease - Pusparini Habsari; Dian Ariningrum; Laily Shofiyah (Green Publisher Indonesia, 2024)
Diabetic kidney disease (DKD) is a long-term complication of diabetes mellitus (DM). The gold standard for diagnosis of DKD is kidney biopsy, but it is difficult to perform. Several clinical conditions have found an association between higher ANGPTL4 plasma levels in DKD. Methods: A total of 87 patients with Type 2 DM were analysed using an observational analytic method with a cross-sectional design. The study subjects were divided into DKD and non DKD groups, then serum ANGPTL4 was measured using the sandwich ELISA method. Furthermore, ANGPTL index cutoff was determined. Several other variables including glycemic control, duration of DM, history of hypertension, and dyslipidemia were analysed for their association with DKD and non DKD groups. The study continued by conducting multivariate analysis with logistic regression. Results: A total of 23 (26.4%) subjects were classified as DKD and 64 (73.6%) subjects as non DKD. ANGPTL cutoff determination of 16.64 ng/mL had a sensitivity and specificity of 87% and 51.6%, respectively. Bivariate analysis showed glycaemic control, duration of DM, and serum ANGPTL4 (p=0.044; p=0.009; p=0.014) were associated with the incidence of DKD. Multivariate analysis showed that serum ANGPTL4 with a cutoff of >16.64 ng/mL could be used as an independent predictor of DKD incidence with an adjusted OR of 6.73 (95%CI= 1.79-25.30; p=0.005). Conclusion: serum ANGPTL4 is an independent predictor of DKD. Suggestion: Urine sampling for UACR examination twice, periodic examination of serum ANGPTL4 levels to assess the progressiveness of DKD.